Coronary Microvascular Spasm: Clinical Presentation and Diagnosis - Shigeo Godo; Jun Takahashi; Takashi Shiroto; Satoshi Yasuda; Hiroaki Shimokawa (European Cardiology Review)
Professor Maseri pioneered the research and treatment of coronary vasomotion abnormalities represented by coronary vasospasm and coronary microvascular dysfunction (CMD). These mechanisms can cause myocardial ischaemia even in the absence of obstructive coronary artery disease, and have been appreciated as an important aetiology and therapeutic target with major clinical implications in patients with ischaemia with non-obstructive coronary artery disease (INOCA). Coronary microvascular spasm is one of the key mechanisms responsible for myocardial ischaemia in patients with INOCA. Comprehensive assessment of coronary vasomotor reactivity by invasive functional coronary angiography or interventional diagnostic procedure is recommended to identify the underlying mechanisms of myocardial ischaemia and to tailor the best treatment and management based on the endotype of INOCA. This review highlights the pioneering works of Professor Maseri and contemporary research on coronary vasospasm and CMD with reference to endothelial dysfunction, Rho-kinase activation and inflammation.